2022
DOI: 10.1002/pros.24410
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids are induced while dihydrotestosterone levels are suppressed in 5‐alpha reductase inhibitor treated human benign prostate hyperplasia patients

Abstract: Background The development of benign prostatic hyperplasia (BPH) and medication‐refractory lower urinary tract symptoms (LUTS) remain poorly understood. This study attempted to characterize the pathways associated with failure of medical therapy for BPH/LUTS. Methods Transitional zone tissue levels of cholesterol and steroids were measured in patients who failed medical therapy for BPH/LUTS and controls. Prostatic gene expression was measured using qPCR and BPH cells were used in organoid culture to study pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 47 publications
7
29
0
Order By: Relevance
“…11 We reported that BPH patients, who underwent surgical intervention to relieve LUTS due to failure of a 5ARI or an α-blocker plus 5ARI, had high transition zone (TZ) tissue levels of testosterone (T), low levels of tissue dihydrotestosterone (DHT), and diminished activation of the androgen receptor (AR). 12 These findings confirmed that a 5ARI continues to block androgenesis in men who fail medical therapy suggesting that the mechanism of growth is independent of AR activation. However, 5ARI treatment raised prostatic tissue levels of glucocorticoids (GC), whereas BPH patients on α-blocker or no drug showed low levels of glucocorticoids.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…11 We reported that BPH patients, who underwent surgical intervention to relieve LUTS due to failure of a 5ARI or an α-blocker plus 5ARI, had high transition zone (TZ) tissue levels of testosterone (T), low levels of tissue dihydrotestosterone (DHT), and diminished activation of the androgen receptor (AR). 12 These findings confirmed that a 5ARI continues to block androgenesis in men who fail medical therapy suggesting that the mechanism of growth is independent of AR activation. However, 5ARI treatment raised prostatic tissue levels of glucocorticoids (GC), whereas BPH patients on α-blocker or no drug showed low levels of glucocorticoids.…”
Section: Introductionsupporting
confidence: 53%
“…Since patients on a 5ARI showed elevated levels of glucocorticoids (GS) and decreased levels of dihydrotestosterone (DHT), 12 we compared the 5ARI (n = 6) and α-blocker plus 5ARI (n = 7) patients to a combined group of patients on no medical therapy (none: n = 7)…”
Section: Transcriptomic Analysis Of 5ari363 Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with controls, androgen-depleted animals have lower bacterial counts and inflammation, reducing the risk of BPH development. 417,418 Recent research also suggests that BPH may be an immuneinflammatory disease. Approximately 90% of prostate immune cells are T lymphocytes, which promote the release of cytokines and growth factors.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%